Simulating Strength Behaviors of Corner Joints of Wood Constructions by Using Finite Element Method - Bulent Kaygin (University of Zagreb, Faculty of Forestry and Wood Technology, 2016)
Using finite element method (FEM) has become wide spread in the field of wood mechanics for analyzing difficult problems instead of conventional methods. The objective of this study is to determine the strength properties of wood corner joints using FEM. For this purpose, diagonal compression and diagonal tension experiments were carried out using dowel, mortise and tenon elements. Corner joints (L-type) were prepared with Scotch pine (Pinus sylvestris L.) and Beech (Fagus orientalis Lipsky) woods. Data obtained experimentally were used in FEM computer modeling to determine structural specifi cations of wood materials. The amount of deformation as a result of compression-tension in the corner joints was determined and then simulated with a computer program using FEM (ANSYS Multiphysics/LS-DYNA). As a result, the amount of deformation obtained from experiments was consistent with the FEM computer modeling with 90 to 97 %. It is suggested that strength properties of joints can be forecast by using FEM computer modeling instead of physical experiments that may cause loss of time, increase of cost and destruction of materials.